НОВЫЕ ПЕРСПЕКТИВЫ МЕТОДА КАРДИОСИНХРОНИЗИРОВАННОЙ ПНЕВМОКОМПРЕССИИ ДЛЯ ЛЕЧЕНИЯ СЕРДЕЧНО-СОСУДИСТЫХ ЗАБОЛЕВАНИЙ - В. В. Резван; Д. Л. Виноградов; А. М. Шкляров (SINAPS LLC, 2015)
In recent years, thanks to the work by Russian specialists Enhanced external counterpulsation expanded scope. In addition to the treatment of various forms of coronary heart disease, it showed good results in the treatment of peripheral vascular disease. The paper presents the current data on the results of the use of the method in various vessels diseases.